Cryptomeria pollen abundance and a new chronologic framework of core SG06 from Lake Suigetsu (Japan) since 146 ka - Nakagawa, Takeshi; Francke, Alexander; Tyler, Jonathan James; Staff, Richard A; McLean, Danielle; Nowinski, Vanessa; Saito-Kato, Megumi; Tibby, John; Ikehara, Minoru; Yokoyama, Yusuke; Gotanda, Katsuya; Haraguchi, Tsuyoshi; et al. (PANGAEA, 2025)
We present new Cryptomeria pollen abundance back to the penultimate glacial period (146 ka). The sediments down to a maximum penetration depth of 73m were recovered in summer 2006 using a hydro-pressure thin-walled piston sampler and a floating platform by the Suigetsu 2006 Project Members. A new chronology for the Lake Suigetsu's sediments were developed beyond the well-constrained radiocarbon limit based on (1) tephrochronology, and (2) tephrostratigraphy, and (3) careful alignment of Cryptomeria pollen abundance between Lake Suigetsu and marine core MD01-2421 located in the northern Pacific Ocean. Additional palaeoclimate data from Lake Suigetsu (Japan) core SG06 including total organic carbon (TOC), total nitrogen (TN), TOC/TN ratios, carbon isotope analyses of organic carbon (δ13Corg) are also presented in accompanying publications to reconstruct orbital-scale monsoon dynamics in Japan.
Keywords: Asian Monsoon; chronology; Japan; Lake Suigetsu; Organic Geochemistry; stabe isotopes